A comparison study of NTB and medium lantern slide emulsions for autoradiographs - Boyd, George A.; University of Rochester.; U.S. Atomic Energy Commission. (U.S. Atomic Energy Commission, Technical Information Branch, 1949)
The grain speed of Eastman NTB and medium lantern slide emulsions were compared by exposing to a known number of I(131) beta particles. Grains were counted. On the basis of this work and unpublished work by the Eastman Kodak Research Laboratories, an I(131) beta particle has equal probability of rendering a grain developable in the present NTB emulsions as in the medium lantern slide, even though the latter are larger. The NTB fog is low and resolution high.
Work performed at the University of Rochester.
"Date Declassified: July 9, 1948."
"AECD-2106."
Title from cover.
Includes bibliographical references (p. 5).
Keywords: Emulsions. / http://id.loc.gov/authorities/subjects/sh85042950; Autoradiography. / http://id.loc.gov/authorities/subjects/sh85010463